Higher Education in East Asia: Challenges for the Present and the Future - Horta, Hugo (International Higher Education, 2024)
The expansion of higher education systems in East Asia is largely coming to an end, and postmass education is becoming a reality. This transition involves a set of challenges that will require education policies, universities, and other relevant agents to adapt to new circumstances in an environment shaped by demographic and techno-economic shifts. Research will also need to become more collaborative, international, and multidisciplinary to meet the complex and uncertain challenges of the twenty-first century.